Serum Cholesterol, Triglyceride, and Ghrelin Levels in Criminal and Non-criminal Schizophrenia Patients - Turkoglu, Abdurrahim; Tokdemir, Mehmet; Atmaca, Murad; Namli, Mustafa; Ustundag, Bilal (Kure Iletisim Grubu A S, 2009)
Objective: Crime is described as actions that disturb the legal order in the community, violate the ethical codes of the society or hinder public interest. Among all psychiatric diseases, schizophrenia is recognized for its association with aggressive behaviors. Some biochemical parameters are considered to induce crime and aggressive behaviors in schizophrenia patients. In this study, we aimed to compare the levels of serum cholesterol, triglyceride, and ghrelin of schizophrenia patients who have committed and not committed a crime and to analyze their effects on commitment of a crime. Method: The current study included 50 schizophrenia patients with at least one record of crime and 50 schizophrenia patients without a crime record that were all diagnosed and treated in Elazig Mental Hospital. All patients completed a sociodemographic information form. Blood samples for total cholesterol, triglyceride, and ghrelin levels were obtained between 08.00 AM and 11.00 AM. Results: Serum triglyceride and ghrelin levels were higher in the schizophrenia patients that have committed a crime compared to schizophrenia patients that have not committed a crime. Difference between triglyceride and ghrelin levels was statistically significant. Levels of serum total cholesterol were lower in the schizophrenia patients that have committed a crime; however the difference was not statistically significant. Discussion: Our findings have suggested that some biochemical parameters may be important for crime tendency in schizophrenia patients. Further studies are required to confirm the reliability of these parameters for committing a crime. We believe that cholesterol and ghrelin levels will help clinicians for better management of crime tendency in these patients.
Keywords: schizophrenia; cholesterol; triglyceride; ghrelin; crime tendency